2018
DOI: 10.1093/jac/dky380
|View full text |Cite
|
Sign up to set email alerts
|

Association between HIV-1 subtype and drug resistance in Nigerian infants

Abstract: This dataset reveals differences among SDRMs by subtype; in particular, between the GWA-II and GCA subclades, compared with CRF02_AG and GWA-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…We observed a high prevalence of RAMs to NRTIs (up to 77% in children and adolescents) and NNRTIs (nearly 50%) in the three demographic groups, whereas the prevalence of RAMs to PIs and INSTIs was relatively low or absent. Our findings confirm the situation previously described in the WHO 2019 HIVDR report [ 1 ], as well as other recent studies from the West Africa region, including our previous study describing HIVDR among adult PLWH in Sierra Leone [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed a high prevalence of RAMs to NRTIs (up to 77% in children and adolescents) and NNRTIs (nearly 50%) in the three demographic groups, whereas the prevalence of RAMs to PIs and INSTIs was relatively low or absent. Our findings confirm the situation previously described in the WHO 2019 HIVDR report [ 1 ], as well as other recent studies from the West Africa region, including our previous study describing HIVDR among adult PLWH in Sierra Leone [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Several other studies from the West and Central Africa WHO region have reported high DRM rates, e.g. : 63% to NRTIs and 71% to NNRTIs in patients failing ART in Liberia; 9 70%, 93% and 68% in Senegal, Mali and Guinea-Conakry, respectively; 10 21.7% to NRTIs and 44.8% to NNRTIs in infants in Nigeria; 11 and up to 60% in a Guinea-Bissau cohort 12 . Thus, there are high levels of DRMs to NNRTIs, which currently constitute the recommended first-line ART in these countries.…”
Section: Introductionmentioning
confidence: 93%
“…We previously showed that gag-protease -derived phenotypic susceptibility differed between CRF02_AG and subtype G-infected patients who went on to successfully suppress viral replication versus those who experienced virological failure (VF) of lopinavir/ritonavir monotherapy as first-line treatment in a clinical trial 12 . In order to determine the relevance of this finding for real-world settings in the context of tenofovir disoproxil fumarate + lamivudine or zidovudine + lamivudine with ritonavir-boosted PI (lopinavir or atazanavir) we analysed the relationship between PI susceptibility and the outcome of PI-based second-line ART in Nigeria, where subtypes CRF02_AG and G dominate the epidemic 24 …”
Section: Introductionmentioning
confidence: 99%